2013
DOI: 10.1111/jace.12277
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polyvinylpyrrolidone Additions on the Rheology of Aqueous, Highly Loaded Alumina Suspensions

Abstract: The control of the rheological behavior of highly loaded ceramic/polymer suspensions affords the development of near-net shape forming techniques. In this study, suspensions containing sub-micrometer diameter alumina (up to 56 vol%) were fabricated using an anionic dispersant (%4 vol%) and water-soluble polyvinylpyrrolidone (PVP). The amount and ratio of molecular weights of PVP in the suspension were varied to influence flow behavior. The final pH of the system, %9.5, was higher than the isoelectric point (IE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 59 publications
1
33
0
Order By: Relevance
“…An increase in the solids loading has been shown to increase the viscosities of ceramic suspensions due to an increase in the inter-particle interactions and inter-particle collisions [15,32,37,38]. A study with aqueous alumina suspensions dispersed with polyvinylpyrrolidone showed that an increase in polymer molecular weight increased the viscosity of the suspensions due to the increase in chain entanglements [18,34,35].…”
Section: Rheological and Viscoelastic Characterization Of Suspensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in the solids loading has been shown to increase the viscosities of ceramic suspensions due to an increase in the inter-particle interactions and inter-particle collisions [15,32,37,38]. A study with aqueous alumina suspensions dispersed with polyvinylpyrrolidone showed that an increase in polymer molecular weight increased the viscosity of the suspensions due to the increase in chain entanglements [18,34,35].…”
Section: Rheological and Viscoelastic Characterization Of Suspensionsmentioning
confidence: 99%
“…Once the applied shear stress exceeds the yield stress, the suspension flows and parts can be constructed by rastering the extrudate in a controlled fashion, building up the part layer by layer. Upon removal of the shear stress the yield stress of the suspension quickly develops again, prohibiting the formed part from slumping due to either gravity or its own weight [9,15,[17][18][19]. Suspensions are typically designed with high solids loading for two reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Using a previously developed suspension formulation, ceramic suspensions composed of a ceramic powder, dispersant, polymer binder, and water can be utilized for direct writing complex ceramic objects. Alumina has been used in preliminary experiments as a model material due to its low cost, availability, and ease of densification.…”
Section: Introductionmentioning
confidence: 99%
“…Alumina has been used in preliminary experiments as a model material due to its low cost, availability, and ease of densification. Previous studies have optimized alumina suspensions using PVP as a binder and a cationic polyelectrolyte as a dispersant. In prior work, PVP has been shown to increase green body strength and machinability of alumina parts prepared by room‐temperature injection molding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation